PRIDE AND PUNISHMENT: THE CHURCH, THE STATE, AND PRIDE PARADES IN SERBIA (2012-2024) (Религиски дијалог и соработка, 2025)
A process of desecularization, sacralizing the nation, and retraditionalizing gender roleshas been ongoing in post-Yugoslav Serbia since the late 80s, but has gained new steam since 2012,when a new government of a coalition similar to the 1990s politics was formed, albeit this timewith the ostensible aim of joining the EU. Against the backdrop of these processes, Serbian identityhas been constructed in a particularly masculine way. And although the use of homophobiato Other the ‘Enemy within’ is not new in Serbian nationalism, a notable shift has been observedas Serbia has been pushed to accept LGBT bodies as part of its Europeanisation process, which isnow further complicated by the war in Ukraine. The pride parades, which Serbia has had to enduredue to its European integration process, and the tactical decision to appoint a lesbian prime minister,have contributed to the impossibility to openly rely on stereotypical homophobic means ofothering. As such, the focus of the ‘enemy’ within shifted from the homosexual to other ‘Others’:Albanians, migrants traversing the Balkan route, non-maternal women, and most recently, ‘genderideology’ in biology textbooks and gender-sensitive language. Tracing the debates in the Serbianmedia, especially with regard to the discursive chasm between LGBT communities/feminisms andthe Serbian Orthodox Church, but also with changes in the dominant media discourse, this papercontends that nationalist othering in Serbia is consistently reshaped in order to accommodatethe changing political climates. It demonstrates the moving boundaries in the construction of thenation, which constantly fluctuating representations of identities stereotypically associated withLGBT communities, masculinities and femininities, ‘Serbhood’, and Orthodoxy.